Motorcyclist Safety Risk and Attitude to Using Helmet - Hasan, M F; Mahmud, S M S; Raihan, M A; Akter, A; Bhattacharjee, A (Journal of Engineering Science, 2023)
The quantity of motor-bikers has dramatically expanded in Bangladesh, with the presentation of the ridesharing business. Consequently, crashes involving a motorcycle with fatalities and injuries are also increasing. One of the proven most effective safety measures for a biker is the use of a helmet. But there is no study on the use of helmets and the attitude of users to use the helmet. This research conducts an in-depth analysis of motorcycle safety risk using reported crash records as well as a comprehensive questionnaire survey among the bikers. The study also explores helmet usage attitude and evaluates the standard of the helmet being used. Overall, around 72% self-proclaimed they do not do wrong practice while riding a motorcycle. However, more than one-fourth of motorcycle drivers/riders misbehave or ill practice at different levels either often or always. Concern authorities could gainfully use the findings to develop motorcycle risk management strategies. Journal of Engineering Science 13(2), 2022, 11-20